A inteligência coletiva e a nova percepção da esfera pública a partir da era da pós-verdade: um paradoxo que se impõe - Pissaia, Álan (My University, 2019)
This work focuses on the following research problem: To what extent is the so-called collective intelligence capable of realizing a new perception of the public sphere as we live in the era of the Post-Truth? Under this premise, two directions of hypotheses are based: the principles of the so-called collective intelligence no longer meet the demands of the new media public sphere, considering what has been called the Post-Truth era; From the Post-Truth era, the media public sphere demands a new behavior from the social subjects. From this, the general objective is to study the principles of the so-called collective intelligence Theory, by Pierre Lévy, seeking a comparative with the principles and characteristics of the Post-Truth society. Similarly, the following specific objectives were listed: to study the principles of the so-called collective intelligence theory, based on Pierre Lévy; To study the characteristics of contemporary society, with emphasis on what has been called the Post-Truth era; To draw up a comparative study between the principles of the two theories cited, seeking synergistic points and points where, mainly, from the end of the first decade of the 20st century, a "new model of society" begins to be drawn. In this sense, the research focuses on the qualitative orientation of an analytical nature, which is based on the basis of the bibliographic research and, in a complementary way, the hermeneutics. The main authors triggered for this investigation are Pierre Lévy (2000), Jürgen Habermas (1989; 2003), Gadamer (2004), Ricoeur (1978), Fredric Jameson (1995), Zygmunt Bauman (1998; 2001), Baudrillard (1991), Kuhn (2005) and Guy Debord (1997), among others that serve as support for the realization of this monograph (sic).
Este trabalho se orienta no seguinte problema de pesquisa: até que ponto a chamada inteligência coletiva é capaz de dar conta de uma nova percepção da esfera pública na medida em que vivemos na era da pós-verdade? Sob essa premissa, baseiam-se duas direções de hipóteses: os princípios da chamada inteligência coletiva já não atendem mais às exigências da nova esfera pública midiática, considerando o que vem sendo chamado de era da pós-verdade; a partir da era da pós-verdade, a esfera pública midiática exige dos sujeitos sociais um novo comportamento. A partir disso, o objetivo geral é estudar os princípios da chamada teoria da inteligência coletiva, de Pierre Lévy, buscando um comparativo com os princípios e características da sociedade da pós-verdade. De igual modo, foram elencados os seguintes objetivos específicos: estudar os princípios da chamada teoria da inteligência coletiva, com base em Pierre Lévy; estudar as características da sociedade contemporânea, com ênfase no que vem sendo chamado de era da pós-verdade; traçar um estudo comparativo entre os princípios das duas teorias citadas, buscando pontos sinérgicos e pontos em que, principalmente, a partir do final da primeira década do século XX, começa a desenhar-se um "novo modelo de sociedade". Nesse sentido, a pesquisa incide na orientação qualitativa, de cunho analítico, fundamentando-se na pesquisa bibliográfica como método e, de forma complementar, a hermenêutica. Os principais autores acionados para esta investigação são Pierre Lévy (2000), Jürgen Habermas (1989; 2003), Gadamer (2004), Ricoeur (1978), Fredric Jameson (1995), Zygmunt Bauman (1998; 2001), Baudrillard (1991), Kuhn (2005) e Guy Debord (1997), dentre outros que servem de apoio para a realização desta monografia (sic).
Keywords: Jornalismo; Inteligência coletiva - Aspectos sociais; Individualismo